Effect of 12-Weeks Brisk Walking Exercise Duration on Blood Pressure and VO2max on Overweight and Obese Female Students in Indonesia - HARUN, Iriyani; RIYADI, Hadi; BRIAWAN, Dodik; KHOMSAN, Ali (Nutrición Clínica y Dietética Hospitalaria, 2022)
Abstract Background: Lack of physical activity is one of the causes of the increasing prevalence of overweight and obesity. Therefore, the strategy to overcome this is to increase the physical activity exercise program. The objective of this study was to evaluate the effect of 12 weeks of brisk walking exercise duration on blood pressure and VO2max in overweight and obese female students in Indonesia Methods: The quasi-experimental design of the pre and post-test involved 40 overweight and obese female students aged 20-30 years with a BMI of ≥ 25 kg/m2 who were non randomly recruited and divided into two groups, namely BW-60 (n=19) and BW-40 (n=19). Both groups did exercise five times a week at 50%-75% of maximum heart rate for 12 weeks. Systolic, diastolic, and VO2max were evaluated before and after the intervention. The data analysis was performed by SPSS 21.0 using the Shapiro-Wilk test, independent sample t-test, Paired sample t-test. P<0.05 was to set a level of significant significance. Results: There was a significant increase in VO2max after the intervention program for each group, namely, BW-60 (p<0.001), BW-40 (p<0.001). There was no significant effect on systolic and diastolic blood in both groups (P>0.05) Conclusion: Both BW-60 and BW-40 groups effectively increased VO2max, but there was no significant change in blood pressure parameters. However, more research is needed with longer intervention times and different intensities and types of exercise to further optimize exercise doses for specific health benefits.